A combinatorial study of the effect of Al and Cr additions on the mechanical, physical and corrosion properties of Fe. (December 2021) - Springer, H.; Baron, C.; Tanure, L.; Rohwerder, M.
Abstract: The effects of Al and Cr additions on the mechanical, physical and corrosion resistance of Fe were investigated in a combinatorial approach on a total of 42 alloys with compositions ranging from 0 to 10 wt% of Al together with 0–12 wt% of Cr (in increments of 2 wt%). All alloys were subjected to hardness, tensile, density, Young's modulus and salt-spray testing, along with structural analysis using x-ray diffraction. Selected alloys were additionally analysed with scanning electron microscopy (microstructure) and x-ray photoelectron spectroscopy (corroded surface). Increasing Al additions linearly reduced both density and stiffness, and led to a sudden strengthening above 2 wt% and embrittlement above 8 wt%. Cr additions counteracted the effects of Al on the mechanical and physical properties, and about 4–8 wt% of Cr could be substituted by 8–10 wt% Al for similar protective effects against wet corrosion. A decrease in Cr and increase in Al concentration in the bulk material results in a similar trend within the passive layer, preserving a significant degree of passivity. Evaluation of the comprehensive data by desirability functions allowed to identify most relevant compositions as the basis for the design of lightweight corrosion resistant steels. Graphical Abstract: ga1 Highlights: The combined effect of Al and Cr on mechanical, physical and corrosion properties of Fe is investigated. Al additions lead to reduced density and stiffness, strengthening above 2 wt% and embrittlement above 8 wt%. Cr additions counteract the effects of Al on the mechanical and physical properties. Cr can be substituted by about twice the amount of Al for similar protection against wet corrosion. Desirability functions revealed compositions as the basis for the alloy design of lightweight corrosion resistant steels.